The role of customer service in increasing the competitive ability and competitiveness of service organizations - D. V. Akopyan; I. A. Suvorov (Вестник университета)
The essence of service and service as a product of the service business, including the core of the service, its customized variants, atmosphere, architecture and contact personnel, has been characterized. It has been found out that customer orientation is a key characteristic of a business in the service sector and reflects a combination of understanding of its strategic vectors, its essential characteristics and the vision of the organization through the eyes of the client (internal - employee and external - consumer). It has been determined that a customer-oriented service consists in focusing attention on the customer, rather than on a product-centered marketing strategy. The components of a successful customer-oriented service have been highlighted, based on the quality of services provided, the level of accompanying service, the range of services provided and the availability of after-sales service. It has been noted that nowadays there is a shift in the relationship between sellers and buyers from onetime transactions to long-term partnership relations.